Technology Educators Pedagogical Adjustment in the Post-pandemic Era: A Case Study of Lecturers in the Oil-rich Region, Nigeria - Arikpo, Sampson; Musta’amal, Aede; Usani, Ofem; Igbudu, Chimemezuo; Subramanian, Murugan; Praises Abang, Otonko (Journal of Technical Education and Training, 2024)
During the COVID-19 pandemic, a lot of lecturers switched to teaching online. There is reason to believe that educators’ pedagogy and teaching philosophies would have undergone a significant transformation. This survey, however, was created to examine the pedagogical and philosophical adjustments technology educators made in reaction to COVID-19. Eight technology educators were subjected to in-depth interviews to learn more about their teaching styles and how they handled the shift to online learning. Thematic and pattern analysis was performed on interview transcripts. Instructors made many changes during the changeover, some general and others specific. Based on the results of the interview, indicators point to several possible explanations for their decisions, such as the extent to which the course structure provided change unnecessary, the influence of the instructors’ existing skill set, their desire to preserve the integrity of grades, a set of questions to help lecturers restructure their curricula, and their understanding of the bounds of technology-based education pedagogy. These interviews help us understand how technology educators were affected by the sudden shift to online instruction. To meet the demands of COVID-19, technology education evolved quickly. However, constant adaptation is required to further improve pedagogy.